Investigating STEM Career Interests: How Can Spatial Orientation, Mental Rotation, and Spatial Visualization Explain Them? - Saputra, Andari; Priatna, Nanang; Dahlan, Jarnawi Afgani; Husni, Niakmatul (Universitas Muhammadiyah Mataram, 2025)
Spatial ability plays a crucial role in shaping students' interest and career paths in STEM (Science, Technology, Engineering, and Mathematics). This quantitative study involved 60 science students aged 15–17 in Bandung, Indonesia, utilizing a spatial ability test to measure mental rotation, spatial visualization, and spatial orientation, along with a career interest questionnaire to assess STEM and non-STEM preferences. Logistic regression analysis confirmed that spatial ability significantly influenced students' STEM interest (p = 0.004) with a moderate contribution. Further analysis using the Independent Samples T-Test revealed that students interested in STEM had significantly higher mental rotation (p < 0.001, Cohen’s d = -1.000) and spatial visualization (p = 0.002, Cohen’s d = -0.797) abilities than non-STEM students, while spatial orientation showed no significant difference (p = 0.112, Cohen’s d = -0.317). These findings highlight the role of spatial ability as a predictor of STEM interest, emphasizing the need for educational interventions such as visualization-based learning, three-dimensional object manipulation, and technology-assisted spatial training, including computer-aided design (CAD) software and mental rotation exercises. Integrating these strategies into mathematics and science curricula can enhance spatial skills and support students' engagement in STEM education and careers.